2020
DOI: 10.3897/bdj.8.e49535
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of Rhinonyssid mites (Mesostigmata: Rhinonyssidae) in Northwest Russia: New mite-host associations and prevalence data

Abstract: Rhinonyssid mites are permanent parasites of birds that inhabit their respiratory tract. There are around 600 species described worldwide and almost all species of birds are found to have embedded rhinonyssid mites. Despite their presumed relevance, these mites are largely unstudied due to the difficulty in sampling them and, therefore, the majority of mite-host associations and species-prevalence data are unknown. In this study, 179 mite specimens belonging to 27 species and eight genera were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…To our knowledge, this is the first paper that explores these estimates for M. streptopeliae. Regarding M. columbae, only three publications explore this kind of data: Crossley (1952), who reported a prevalence of 20% in 60 pigeons [52]; Wilson (1964), who found a prevalence of 7% after examining 15 pigeons [23]; Rojas et al (2020), who found a prevalence of 1.9% after examining 262 pigeons in St. Petersburg (Russia) [48]. Meanwhile, we found a prevalence of 6%.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…To our knowledge, this is the first paper that explores these estimates for M. streptopeliae. Regarding M. columbae, only three publications explore this kind of data: Crossley (1952), who reported a prevalence of 20% in 60 pigeons [52]; Wilson (1964), who found a prevalence of 7% after examining 15 pigeons [23]; Rojas et al (2020), who found a prevalence of 1.9% after examining 262 pigeons in St. Petersburg (Russia) [48]. Meanwhile, we found a prevalence of 6%.…”
Section: Discussionmentioning
confidence: 56%
“…The morphological information published until now on rhinonyssids is abundant but not very detailed, and the illustrations are not as exhaustive as the ones we provide. Furthermore, epidemiological studies are frequently based on the analyses of a few hosts, which makes the epidemiological survey inaccurate due to the low prevalence of the species studied [9][10][11][12][13] (but see [48]). We offer a detailed survey of the nasal mite species found in 250 C. livia domestica and 250 S. decaocto.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On some occasions, mites have an intimate association (symbiosis) with a different organism, which, in the most extreme scenario (permanent symbionts), represents the habitat in which they undergo their entire life-cycle [9]. For example, a single species of insect, mammal, or bird can often host several mite species and have different types of interactions with them [9,[10][11][12]. The nature of these interactions can range from mutualism (e.g., mites inhabiting and cleaning birds' feathers; [13]) to parasitism (e.g., mites inhabiting the nasal passages and lungs of seals causing illness to them; [14,15]).…”
Section: Introductionmentioning
confidence: 99%